2019
DOI: 10.1039/c9ta06686a
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Ni-based layered double hydroxides as high-efficiency electrocatalysts for the oxygen evolution reaction: a DFT study

Abstract: The development of high-activity and earth-abundant non-noble metal electrocatalysts for the oxygen evolution reaction (OER) is highly desirable but is an ongoing challenge facing us now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 53 publications
3
48
0
Order By: Relevance
“…NiOOH has been shown as a catalyst for OERs [36,37,66], and the exposed surface O sites play a vital role for its OER activity [49]. In the present work, we showed that the O sites on the NiOOH surface can activate the C-H bonds of propane.…”
Section: Selectivity Of Propylenesupporting
confidence: 55%
See 1 more Smart Citation
“…NiOOH has been shown as a catalyst for OERs [36,37,66], and the exposed surface O sites play a vital role for its OER activity [49]. In the present work, we showed that the O sites on the NiOOH surface can activate the C-H bonds of propane.…”
Section: Selectivity Of Propylenesupporting
confidence: 55%
“…Nickel oxide hydroxide (NiOOH) is a precursor to the preparation of NiO and has been widely investigated for oxygen evolution reactions (OERs) in electro/photocatalytic water splitting systems [35][36][37][38]. NiOOH shows high activity for water oxidation, which is rate limiting for the electrocatalytic water splitting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Fe-free Ni oxides, NiOOH and especially its g phase are often described as potential active electrocatalysts for the OER. 42,43 In particular, g-NiOOH has a layered structure consisting of NiOOH planes and intercalated water molecules or ions, with a larger interplanar distance than b-NiOOH. 44,45 This results in a higher Ni oxidation state in g-NiOOH (3.5-3.67) than in b-NiOOH (3), and thus in a superior catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that *OOH species are the vital intermediates in enhancing the OER activity, even if the formation of these species is a kinetically challenging step, as suggested by DFT calculations. [47,48] The effect of electronic modulation on the OER/hydrogen evolution reaction (HER) rates is well-reported in literature, and here the electronic modulation of Co sites, induced by the unique interplay of electrons, facilitates the formation of CoOOH species. [49][50][51] In the case of CoÀ MoÀ PB, the simultaneous inclusion of Mo, P and B creates a synergistic effect to generate the maximum number of active CoOOH species at lower potential, leading to highest OER activity.…”
mentioning
confidence: 85%